Service landscape for private universities in indonesia based on service oriented architecture and cloud technology - Faiza Renaldi; Irma Santikarama; Esmeralda C. Djamal; Agya Java Maulidin (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Information technology (IT) has been widely adopted and is believed to improve academic processes’ efficiency and run private universities’ academic functions (PTSs) in Indonesia. Nonetheless, adopting diverse technologies for them will also create many challenges. PTSs are struggling to survive in terms of technological implementation, in the sense that the investment and implementation rate in the PTSs just cannot catch up with the technological advancement rate. Even when more PTSs are trying to transform into digital entities, the next problem will be system integration and flexibility. This study aims to overcome this problem by implementing a framework that can be both integrated and flexible while also serving the efficiency of investments. Many studies already suggested that service oriented architecture (SOA) and cloud technology are the solutions. Nevertheless, none has been able to define what standard services can be applied within those platforms. To determine this, we use the BIAN service landscape, which was translated from the banking industry, offering a comprehensive view of the business domain and business capabilities alongside its service functions. While BIAN offers common services throughout the same platform, we modify the framework using the OASIS model from SOA, which allows the framework to be flexible in complying with many platforms of databases, programming languages, and network infrastructures. We completed our study by defining one business area: academic processes, three business domains, 19 business capabilities, and 84 service functions. We are strongly confident that our findings and study results will act as a reference in creating a cloud-based platform for Indonesia’s higher education academic systems.